Peer review: A highly valuable service but less recognized - Asegid Getachew Woldeamanuel (Journal of Innovation and Entrepreneurship)
Abstract Peer review is an independent process of checking the quality and rigor of articles submitted to a journal. It is considered as a hallmark of the reputability and excellence of a journal. Peer reviewers spend a significant portion of their time and energy to assess the significance, originality and rigor of manuscripts and thereby help editors make an informed decision. The review process, typically enhances the quality and relevance of submitted manuscripts. Needless to say, Peer reviewers play a crucial role in ensuring research is done following accepted scientific procedures and sound methodologies. However, the contribution that previewers make to the advancement of knowledge has not sufficiently been recognized. I argue that it is unjustifiable to consider the free services of peer reviewers for granted. I also propose alternative ways of recognizing the efforts of peer reviewers.